An ethnopharmacological evaluation of Navapind and Shahpur Virkanin district Sheikupura, Pakistan for their herbal medicines - Maria Zahoor; Zubaida Yousaf; Tahreem Aqsa; Manahil Haroon; Nadia Saleh; Arusa Aftab; Sadia Javed; Mouzma Qadeer; Habiba Ramazan (BMC, 2017)
Abstract Background The chief aim of this study was to enlist the ethnobotanical uses of wild plants in district Sheikhupura, province Punjab, Pakistan. Due to extreme geographical and climatic conditions, Pakistan has a great floral diversity. Plants have been used by the indigenous people for treatment of different ailments since long. They are still dependent on the plants for their domestic purposes. Moreover, plants are used as first aid to treat diverse ailments such as cold, cough, influenza, asthma, cancer, antidote, gastric and hepatic disorders. The traditional uses of medicinal plants lead to the discovery of natural drugs. This is first quantitative ethnobotanical documentation of medicinal plants in NavaPind and ShahpurVirkan district Sheikhupura, province Punjab, Pakistan. Methods This ethnobotanical information was collected from about 400 informants including male and female. Sample size was determined by statistical formula. The informative data was based on semi-structured interviews, group discussions, Questionnaire and field visits. Then the data was analyzed by applying different quantitative indices such as Informant Consent Factor (ICF), Use value (UV), Relative Frequency of Citation (RFC), the Fidelity level (FL) and Jaccard Index (JI). Results Almost 96 plants belonging to 34 families were reported. Most-frequently cited families were Poaceae (16 species) and Fabaceae (15 species). The most dominant life form was herbs (30.20%). The most-used plant parts were leaves (31.14%), followed by whole plant (24.59%), Most common mode of administration is extraction (81.25%). Generally herbal medicines were acquired from fresh plant material. Among all 54.16% plants were toxic, 31.25% were nontoxic, whereas the remaining 14.58% may be toxic or nontoxic because of their dual attitude. Almost 34 species were reported with their different medicinal uses as has been reported in literature. Conclusions This ethnobotanical documentation revealed that the plants are still used by natives of rural areas in their day-to-day lives. This study provides basis for the conservation of local flora. Plants with high ICF, UV and FL can be further used for phytochemical and pharmacological studies. This documentation could provide baseline information which can be used to develop new plant-based commercial drugs.